THE PHENOMENON OF DONALD TRUMP AND SCENARIOS OF US-RUSSIAN RELATIONS - A. O. Bezrukov; A. A. Sushentsov (Сравнительная политика, 2018)
This article examines the foreign policy platform of Donald Trump,  based on his proposals, the composition of his advisers and  supporting coalitions. Second focus of the article is the internal  political context and limitations to the new administration of the  White House. Finally, there are conclusions for Russia and possible  scenarios for the development of bilateral relations after the  inauguration of Donald Trump. The future of Russian-American  relations is the key uncertainty of 2017. Russian foreign policy  greatly depends on it. The development of relations can go in several directions, which is conditioned to success or failure of Trump domestic economic program, as well as high or low level of conflict  behavior of new US administration in its foreign policy. From the  perspective of economic and internal policy the criterion of success for Trump will be the speed with which he could launch a legislative mechanism for tax reform and infrastructure investment  despite the Democrats opposition. From the perspective of foreign policy, the main uncertainty in US-Russia relations will be  about the future of confrontation in Eastern Europe and willingness  of the parties to cooperate in stabilizing the situation in the Middle East, despite the differences in objectives and choice of allies. A key condition for normalizing relations remains the  preservation of strategic balance between Russia and the United States.